Manifest West: women of the West - Seeling, Caleb, editor; Western Press Books, publisher (Colorado State University. Libraries, 2017)
The editorial term of Manifest West is proud to offer a diversity of voices in this volume that celebrates Western women as an inclusive category, not a stark label. Both female and male authors and poets share their observations and interpretations. We explore the experiences of Hispanic, First Nations, and even Thai women of the West. Their narratives include mothers, daughters, straight women, gay women, and women whose stories refuse to be defined by romance and family, instead spotlighting their passions as hobbyists, workers, and humans.
Women of the West
Introduction -- Inheritance. Manifest / Kierstin Bridger -- Moving West / Debbie Day -- The Rancher's Third Marriage / David Lavar Coy -- Slut / Lisa Levine -- A Woman Can / Corinna German -- Annie Oakley / Paula Bramlett -- Cow Women / Don Cadden -- The Navajo Woman / David Lavar Coy -- Changing Woman / Robert Kostuck -- If Women Ran the World / Ellaraine Lockie -- Remnants, pt. III / Leah Hedrick -- Western Woman / Riashantae Sides -- ... Treasure / Harrison Candelaria Fletcher -- Witches of the West / Ellaraine Lockie -- Sunflower Women / Anita Cruse -- Album. Emma's Seeds / Carolyn Dahl -- When She Speaks / Harrison Candelaria Fletcher -- Grandma's Apron / David Lavar Coy -- My Vietnam Blessing / Cindy L. Prater -- Apron / Gail Denham -- Homesteading in Paradise / Sally Clark -- A Circle of Family / Rick Kempa -- ... Rosewater / Harrison Candelaria Fletcher -- Mean Time, Prime Time / Kathleen Winter -- Boss Over the Bull / Carolyn Dahl -- Gust. My Galapagos / Annie Lampman -- Bleeding in the Wilderness / Betsy Bernfeld -- The Swallows / Rick Kempa -- A Mother's Guide to Birds and Boys / Annie Lampman -- ... Empty Spaces / Harrison Candelaria Fletcher -- Torn. Lonely Vigil in Colorado / Gail Denham -- An Only Daughter Walks with Her Father / Jessica McDermott -- The Darkest / Lisa Levine -- An Incident at Big Sandy Creek, 1864 / Don Kunz -- Grandma Sits Down / Rick Kempa -- The House on Willamette Falls Drive / Scot Siegel -- Basic Nostalgia / Paula Coomer.
A literary anthology 2017
Keywords: Western stories; Women -- West (U.S.) -- Fiction; Women -- West (U.S.) -- Poetry; West (U.S.) -- Fiction; West (U.S.) -- Poetry